Metabolomics approach using LC-Orbitrap high resolution mass spectrometry and chemometrics for authentication of beef meats from different origins in Indonesia - Anjar Windarsih; Abdul Rohman; Nor Kartini Abu Bakar; Erwanto, Yuny (Penerbit Universiti Kebangsaan Malaysia, 2023)
Beef is one of the favourite meats consumed by people worldwide due to its high nutrition value needed by human development. It is highly susceptible for the adulteration practice by substituting beef with lower price meats by unethical meat traders due to the economic reasons. Therefore, the authenticity of beef meat (BM) is important because it is also related to halal status of meat which is required for certain religions. This research aimed to differentiate metabolites of BM from different origins using liquid chromatography-high resolution mass spectrometry (LC-HRMS) combined with chemometrics for the authentication purposes. Various metabolites mostly amino acids and lipids could be detected using methanol extraction. Principal component analysis (PCA), partial least square-discriminant analysis (PLS-DA) and sparse PLS-DA were successfully used to discriminate BMs from different origins. Fifty potential metabolite markers which are important for discrimination have been identified using variable importance projection (VIP) value extracted from PLS-DA analysis. Metabolites of (4S)-4-{[(9Z)-3-Hydroxy-9-hexadecenoyl] oxy}-4-(trimethylammonio)butanoate, N,N-Diisopropylethylamine (DIPEA), D-sphingosine, (2E,4Z)-N-Isobutyl- 2,4-octadecadienamide, 1-(14-methylhexadecanoyl)pyrrolidine, linoleic acid, 12-HAS, dodecylamine1, myristamide, and tributyl phosphate had high responsibility in discriminating BMs from different origins (VIP value > 2.0). It can be concluded that LC-HRMS based untargeted metabolomics combined with chemometrics could be used for authentication of BMs from different regions.